2009
DOI: 10.1542/peds.2008-1578j
|View full text |Cite
|
Sign up to set email alerts
|

Recently Trained General Pediatricians: Perspectives on Residency Training and Scope of Practice

Abstract: OBJECTIVE. Because of the increase in both the prevalence and complexity of chronic diseases in children, there is heightened awareness of the need for general pediatricians to be prepared to comanage their patients with chronic disorders with subspecialists. It is not known currently how well prepared general pediatricians believe themselves to be for these roles after residency training. This study was conducted to determine the perspectives of recently trained general pediatricians in practice regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
94
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 23 publications
2
94
1
1
Order By: Relevance
“…Previous work has estimated that as many as 40% of specialty visits could be managed in primary care, 40 that generalists are more willing to comanage chronic illnesses than subspecialists recognize, 41,42 and that general pediatricians with lower subspecialty access report greater comfort addressing subspecialty care needs. 43 These findings support the possibility that different generalist scope of practice due to different subspecialty supply could account for the small observed difference in utilization without adversely impacting disease burden.…”
Section: Discussionsupporting
confidence: 57%
“…Previous work has estimated that as many as 40% of specialty visits could be managed in primary care, 40 that generalists are more willing to comanage chronic illnesses than subspecialists recognize, 41,42 and that general pediatricians with lower subspecialty access report greater comfort addressing subspecialty care needs. 43 These findings support the possibility that different generalist scope of practice due to different subspecialty supply could account for the small observed difference in utilization without adversely impacting disease burden.…”
Section: Discussionsupporting
confidence: 57%
“…5 In a recent survey of 681 general pediatricians, 1 to 5 years after completion of residency training, 48% reported that they could have benefited from additional training in developmental and behavioral pediatrics, and 18% reported need of additional training in coordination of care of complex illnesses. 6 In addition, a recent Institute of Medicine report on improving healthcare quality identified 'care coordination' and 'children with special health care needs' among the priority areas of focus in transforming the quality of healthcare. 7 Incorporating high-risk infant follow-up care training in pediatric residency curriculum may be useful in addressing these issues at least to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…The Freed et al survey of 7882 pediatrics residents as part of the 2007 American Board of Pediatrics in-training examination 51 sheds light on the pediatrics residency experience. In 3 other articles they examine the perspectives of pediatrics generalists 52 and subspecialists 53 within the first 2 to 5 years after certification, as well as current pediatrics subspecialty fellows 54 regarding their residency experiences and career choices. The tables display the results of additional analyses generated for this commentary: Table 1 compares the answers of generalists and subspecialists to questions about the factors considered in selecting a particular residency program and, generally, how more discretionary, flexible time in residency might be used; Table 2 compares preferences for more learning opportunities in specific content areas; and Table 3 examines the opinions of subspecialists and current fellows regarding the length of time required for residency and fellowship training.…”
mentioning
confidence: 99%
“…For example, Table 1 shows that although geographic location of the residency program was the most important factor for both generalists and specialists, the importance of lifestyle issues, subspecialty expertise/training opportunities, prestige, and patient population varied. Response differences associated with gender, medical school (US or Canadian versus international), size of residency program, and subspecialty are discussed in detail by Freed et al [52][53][54] A second question raised by R 3 P Project participants was: Are current training programs flexible enough to meet training needs both for residents going into general pediatrics and those choosing subspecialty fellowship training? A careful review of the current review committee guidelines for pediatrics reveals a high degree of flexibility, with 8 to 9 months of undifferentiated time across the 33-month (allowing for 3 months of vacation) training period.…”
mentioning
confidence: 99%
See 1 more Smart Citation